Irish Gothics - Morin, Christina. author. aut Link
XI, 215 p.
Keywords: Scholarly interest in 'the Irish Gothic' has grown at a rapid pace in recent years, but the debate over exactly what constitutes this body of literature remains far from settled. This collection of essays explores the rich complexities of the literary gothic in eighteenth- and nineteenth-century Ireland.